Analysis of the Relationship Between Indonesian Language Task Assignment and Student Learning Motivation: A Quantitative Study of Fourth-Grade Elementary School Students - Efrina Hayani; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze and determine the significance of the relationship between giving Indonesian language subject assignments and the level of learning motivation in fourth grade students of State Elementary School 110 Gunungmanaon. The research method used is a quantitative approach with a correlational research design. The population of this study was all fourth grade students of State Elementary School 110 Gunungmanaon, with a research sample of 48 students. The results of the data analysis showed several important findings. First, the quality of giving Indonesian language assignments is in the